Changes in Trade and Domestic Distortions Affecting China's Agriculture - Huang, Jikun (2012)
This paper assesses the implications of China's trade and domestic policies for incentives to producers in China. It uses a price comparison methodology (nominal rates of assistance--at the border and the farmgate), with adjustments for exchange rate distortions in the first part of the sample period (1981-1994). On average, distortions to agricultural incentives have been reduced. In the early 1980s, on average, China's domestic prices were far below international prices. There were substantial variations, however, between imported (which were being protected) and exported goods. During the 1980s and 1990s the gap between domestic and international prices for both imports and exports narrowed initially mainly due to the elimination of domestic policy distortions. Between the mid-1990s and 2004, trade liberalization policy furthered narrowed the gap between world and China farmgate prices. By the mid-2000s, China's agriculture was operating with only small price distortions.